2003
DOI: 10.1094/pdis.2003.87.6.699
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Midseason Pesticide Program for Control of Scab and Plum Curculio in Peach

Abstract: Risks to peach production from scab (caused by Cladosporium carpophilum) and plum curculio (Conotrachelus nenuphar), two key pests in the southeastern United States, are high until 2 months past petal fall and then decreases during midseason. This suggests that reduced-input pesticide strategies may effectively control both pests during the latter period. In this study, we evaluated midseason pesticide applications according to an alternate-row middle (ARM) spray program in which sprays were applied only to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…This observation is in contrast to studies reporting inferior colouration and finish in cv. Blake peaches treated with sulphur‐based programmes compared with captan treated fruit (Scherm & Savelle, 2001; Lan et al , 2003) and to a study by Palmer et al (2003) demonstrating that sulphur applications reduced not only fruit colouration but also leaf photosynthesis of cv. Braeburn apple compared to non‐sulphur treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation is in contrast to studies reporting inferior colouration and finish in cv. Blake peaches treated with sulphur‐based programmes compared with captan treated fruit (Scherm & Savelle, 2001; Lan et al , 2003) and to a study by Palmer et al (2003) demonstrating that sulphur applications reduced not only fruit colouration but also leaf photosynthesis of cv. Braeburn apple compared to non‐sulphur treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Fungicide efficacy studies by others have reported the negative impact of elemental sulphur on fruit quality by reducing colouration (Drake, 1984; Scherm & Savelle, 2001; Lan et al , 2003; Palmer et al , 2003) and increasing fruit russeting (Basak et al , 1983; Sanchez et al , 2001; Steenkamp et al , 1984). In contrast, other studies revealed that elemental sulphur can reduce russeting of apple cv.…”
Section: Discussionmentioning
confidence: 99%
“…The EI was designed to provide growers and weed management practitioners with a single number that indicates the magnitude of relative risk. Despite criticism mainly due to simplicity (Dushoff et al 1994), EI has been used effectively by several researchers to compare environmental risk of different pesticides and/or production systems (Fernandez-Cornejo 1998;Edwards-Jones and Howells 2001;Ziegler et al 2002;Bues et al 2003, Lan et al 2003Brimner et al 2005). The EI can be used as a decision tool, along with herbicide efficacy, crop safety, and profit margins to identify the most advantageous weed management strategy in dry beans.…”
mentioning
confidence: 99%